Interferensi Bahasa Indonesia ke Dalam Bahasa Inggris pada Abstrak Jurnal Ilmiah - Siti Julaika; Edi Syaputra (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to describe the forms and types of interference from Indonesian into English in the abstract of articles in scientific journals. Interference is a form of deviation in language, besides that this study also aims to explain the factors that cause Indonesian language interference when speaking English. The method used in this research is descriptive with a distributional study and pandanus. The data are taken from several scientific journals published by several universities. There are two factors that cause language interference, namely linguistic and non-linguistic factors.